Acquired Unilateral Nevoid Telangiectasia: Dermoscopy and Histopathology Findings of a Rare Dermatomal Vascular Anomaly - Sandra Arora; Sanjeev B Gupta; Nishtha Mishra (Journal of Clinical and Diagnostic Research)
A 26-year-old male presented with an asymptomatic red lesion on the right side of his flank for two months. The lesion gradually enlarged over this period without pruritus, pain, or mucosal involvement. The patient denied alcohol consumption, drug use, recent weight changes, visual disturbances, or any history of cold- or stress-induced worsening. There was no history of birth complications or relevant family history.